Depth Profiling of Block Copolymer Nanostructures in Films by Small‐Angle X‐Ray Scattering Using an X‐Ray Microbeam. Issue 1 (29th May 2013) - Sakurai, Shinichi; Kimura, Go; Mizuno, Yohei; Masunaga, Hiroyasu; Ogawa, Hiroki; Ohta, Noboru; Yagi, Naoto; Adhikari, Rameshwar
Summary We applied the microbeam two‐dimensional small‐angle X‐ray scattering (2d‐µSAXS) technique in order to characterize orientation of polystyrene (PS) microdomains as a function of the distance from the free surface of a sample sheet down to the surface facing to the substrate, for depth profiling for spontaneous perpendicular orientation of PS cylinders in the matrix of polyethylenebutylene (PEB) in a PS‐b‐PEB‐b‐PS triblock copolymer thick sheet as thick as ∼0.5 mm. It has been revealed that near the free surface the cylinders were randomly oriented down to ∼70 µm in depth. Although this might indicate that the surface effect, which preferentially dictates cylinders to be oriented parallel to the surface, can propagate for such a long distance, 70 µm is unusually huge as compared to the general knowledge of the surface effect propagating at most for 1 µm. Experimentally examining further, we finally conclude that the 2d‐µSAXS depth profiling overestimates the surface effect. This unfavorable conclusion may be ascribed to surface roughness of the sample sheet subjected to the measurement, and in order to obtain a good result a big effort is required to prepare the surface as flat as possible.